Feminist Perspectives and Approach in the Novels of Nayantara Sahgal: A Review: Exploring Feminism and Politics in Nayantara Sahgal's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Nayantara Sahgal is a productive writer and her literary standard comprises of eight novels, two collections of memoirs, somenon fictional works. A few articles and short stories of her have been distributed in driving papers and magazines. She is one of India's for most socio-political novelists and her novels present a valid picture of free India. A nearby investigation of her novels uncovers that her two overwhelming themes – social and political are constantly plaited one with the other. She is the main novelist who utilizes legislative issues as a foundation for her social themes. She takes up women's issues as the center to which the political issues frame a background, a thin facade. Her anxiety for women depends more on humanism as opposed to that of feminism. Her feminism does not go past regarding women as a person. To say it quickly, the novels of Nayantara Sahgal manage a wide scope of themes extending from individual quandary and issues, delights and distresses, fulfillment and dissatisfactions of women heroes to the political changes, that India has encountered since freedom.Nayantara depicts the natural right of opportunity for women in a large number of the characters in her novels, for example, Simrit in The Day in shadow, Saroj in Storm in Chandigarh and Rashmi in This Time of Morning. A time to be Happy (1958) and Storm in Chandigarh (1969) are classed as her political novels This Time of morning (1965) Storm in Chandigarh (1969) and The Day in Shadow (1971) are autobiographical to the extent they expand individually passionate encounters and conflicts.